ANALISIS KEBUTUHAN DAN PELAYANAN BIMBINGAN KONSELING DI PONDOK PESANTREN PADA TINGKAT MADRASAH ALIYAH - Mita Sintia; Jumrotur Resty Diana; Muhammad Gibran; Galuh Mulyawan; Ina Salmah Febriani (Jurnal Manajemen Pendidikan, 2026)
Islamic boarding schools, as residential Islamic educational institutions, possess unique social and psychological dynamics. Students at the Madrasah Aliyah (MA) level are in the adolescent developmental phase, a time when they are vulnerable to emotional, social, academic, and career-related issues. The purpose of this study is to identify the needs and services related to guidance and counseling in Islamic boarding schools at the Madrasah Aliyah level. This study employed a descriptive qualitative approach conducted at eight MA Islamic boarding schools in Banten Province. Data were collected through in-depth structured interviews with boarding school leaders and administrators, observations, and the distribution of questionnaires to students. Data analysis was conducted through thematic reduction, presentation, and conclusion-drawing. The results indicate that guidance and counseling services in the boarding schools function effectively through the care system, although most do not yet have dedicated spaces or professional counselors. The range of services includes religious value-based orientation, structured information services, interest-based placement, remedial learning support, responsive individual counseling. These findings underscore the need to strengthen the professionalization and standardization of structured, documented, and needs-based guidance and counseling services, without undermining the boarding school’s values as the foundation of student development.